Simulation of a real-time dual-loop control system for high-quality personalized cardiopulmonary resuscitation. (May 2023) - Sung, Chih-Wei; Chang, Wei-Tien; Chen, Wei-Yu; Jaw, Fu-Shan; Shieh, Jiann-Shing
Highlights: Personalized high-quality cardiopulmonary resuscitation (HqCPR) is important for survival. A dual-control system with real-time chest compression depth and force detection was used. The ultrasonic probe feedbacks compression depth to optimize the chest compression. The pressure sensor protects the machine and carrier from inappropriate compression. This study provided the thought on next-generation chest compression devices in HqCPR. Abstract: An individualized high-quality cardiopulmonary resuscitation (HqCPR) is more beneficial for improving outcomes. The current study aimed to develop a personalized HqCPR system with a standard dual closed-loop feedback control. The dual closed-loop control had features such as distance depth control and compression force protection. An ultrasound probe was used to detect the anteroposterior diameter (APD) in real-time, thereby identifying the next compression depth. An air pump was added to Resusci Anne to adjust the APD during simulation. Next, three springs were added to simulate three different human organs. Four sensors simultaneously detected the force distribution of each compression. The normal operation force range was determined in the pretest stage. Two-min CPR was performed at three different temperatures. The compression depth was almost equal to one-third of the APD of Resusci Anne. There were no significant differences in terms of APD and compression depth between the three different temperatures. The personalized chest compression depth was one-third of the APD, which is the current standard in HqCPR. If the compression force was greater than 1.53–12.52 kg, which is the normal range, the compression system was automatically interrupted. Despite in simulation stage currently, the proposed real-time dual-loop control system provided the feasible for next generation HqCPR mechanical device.